Susceptibility of Grape-vine Rootstocks to Strains of Agro bacterium tumef aciens biovar 3 - Ferreira, J.H.S.; van Zyl, F.G.H. (South African Journal of Enology and Viticulture, 2017)
Forty grape-vine rootstocks were inoculated with five strains of Agrobacterium tumefaciens biovar 3 in a field trial. Grape-vine material like Paulsen 775 was immune to all strains whereas Kober 125 AA, Freedom, 3309 C, Harmony, Solonis, 101-14 Mgt., Berlandieri 13/5 and Kober 5BB appeared to be resistant. Jacquez, US 2-1, US 24-23, Muscat d’ Alexandrie and US 24-10 were the most susceptible. Host range differences occurred among the five strains of A. tumefaciens on the different rootstock cultivars. Five different host range patterns were evident. A. tumefaciens biovar 3 strain 1771 was the most virulent and strain 2221 was the least virulent of the strains used.